2022
DOI: 10.1124/jpet.122.001346
|View full text |Cite
|
Sign up to set email alerts
|

Depression of Synaptic N-methyl-D-Aspartate Responses by Xenon and Nitrous Oxide

Abstract: D-2-Amino-5-phosphonovaleric acid; EGTA, ethylene glycol tetraacetic acid; GABA, γ-aminobutylic acid; HEPES, 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid; I AMPA , I Glu , I KA , I NMDA , AMPA, glutamate, KA, and NMDA receptor-mediated whole-cell currents; KA kainic acid; NMDA, N-methyl-D-aspartate; PPR, paired-pulse rate; Rf, failure rate; s(e)EPSCs, spontaneous and (action potential-evoked) excitatory inward postsynaptic currents; s(e)EPSC AMPA/KA , s(e)EPSC NMDA , AMP/KA (non-NMDA) and NMDA receptor-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Rather, the response was probably mediated by the direct action of the gas on the central nervous system. It is currently well documented by animal-based research, that N 2 O disrupts the function of synaptic transmission ( 58 ), mainly via the inhibition of the N -methyl- d -aspartate glutamatergic receptors ( 56 , 59 61 ), which in turn supresses the release and turnover of dopamine and other catecholamines in selective cerebral structures (i.e., striatum, prefrontal cortex, hippocampus; Refs. 85 , 86 ) that are involved in affective processing, memory, motivation, learning, and executive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the response was probably mediated by the direct action of the gas on the central nervous system. It is currently well documented by animal-based research, that N 2 O disrupts the function of synaptic transmission ( 58 ), mainly via the inhibition of the N -methyl- d -aspartate glutamatergic receptors ( 56 , 59 61 ), which in turn supresses the release and turnover of dopamine and other catecholamines in selective cerebral structures (i.e., striatum, prefrontal cortex, hippocampus; Refs. 85 , 86 ) that are involved in affective processing, memory, motivation, learning, and executive functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that N 2 O affects insignificantly cutaneous thermoreception and axonal conduction (26) and probably does not impair the oxidative capacity of skeletal muscle (i.e., the specific effector end-organ; 27). Considering that N 2 O disrupts the functioning of synaptic transmission (28), primarily via the inhibition of the glutamate N-methyl-D-aspartate (NMDA) receptors (29)(30)(31)(32), it is reasonable to assume that the N 2 O-evoked metabolic downregulation was determined largely by a diminished thermoafferent input (33,34) and/or a modified central integration of CWI C ), while subjects were breathing either room air (AIR) or a normoxic gas mixture containing 30% nitrous oxide (N 2 O). Data were analyzed with a twoway repeated measures ANOVA, followed by Bonferroni post hoc test (P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Xe has been reported to interact with glutamate receptor subtypes such as NMDA, AMPA and KA receptors, especially inhibiting NMDA receptor subtype (Maclver, 2014;Hao et al, 2020). Recently, Kotani et al (2023) also reported that Xe and N 2 O inhibited largely spontaneous and evoked NMDA currents in rat hippocampal CA3 neurons. These previous studies using "synapse bouton preparation" (Akaike and Moorhouse, 2003) of isolated brain and spinal neurons especially indicate that Xe inhibits spontaneous, miniature, and evoked neurotransmissions by acting predominantly on presynaptic nerve terminals.…”
Section: Introduction (574/750 Words)mentioning
confidence: 98%